What Do Academics (Think) They Know About Gold? - LUCEY, BRIAN MICHAEL (London Bullion Market Association, 2011)
A short paper for the LBMA trade newspaper "The Alchemist" this gives a very brief and thus easily accessible survey of some recent academic findings on gold.
PUBLISHED
Keywords: Economics; Gold